Wykorzystanie metody rekurencyjnego podziału do oceny zagrożenia bankructwem polskich przedsiębiorstw - Strąk, Tomasz (Recursive Partitioning in Predicting Corporate Bankruptcy in Poland, 2007)
The paper presents the results of the research which explored the applicability of recursive partitioning to predicting corporate bankruptcy in Poland. Three models were thus constructed. Ml model allows predicting bankruptcy within up to 12 months, M2 model - 12-24 months in advance, and M3 model - 24-36 months in advance. The analyzed company, depending on its present financial performance, can be classified as a high-, medium- or low bankruptcy risk entity. The research shows that only ca. 7% of companies classified as high bankruptcy risk entities will not actually go bankrupt within the period of prediction. The models presented in the paper were constructed on the basis of financial reports of 1147 companies, and then verified on the sample of 945 solvent companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 518-528